Coring, profiling, and trenching: Archaeological field strategies for investigating the Pleistocene-Holocene-Anthropocene continuum. (10th August 2022) - Rick, Torben C.; Alsharekh, Abdullah M.; Braje, Todd J.; Crowther, Alison; Erlandson, Jon M.; Fuller, Dorian Q.; Gill, Kristina M.; Groucutt, Huw S.; Guagnin, Maria; Helm, Richard; Hofman, Courtney A.; Horton, Mark; et al.
Abstract: Archaeologists have long emphasized the importance of large-scale excavations and multi-year or even decades-long projects at a single site or site complex. Here, we highlight archaeological field strategies, termed coring, profiling, and trenching (CPT), that rely on relatively small-scale excavations or the collection of new samples from intact deposits in previously excavated trenches (aka test units or pits). Examples from multiple sites in Africa, Asia, and North America demonstrate that CPT is highly effective for obtaining high-resolution archaeobiological and geoarchaeological samples (e.g., faunal and botanical remains, sediments) and artefacts from areas that have seen limited or no archaeological research, little systematic application of archaeological science methods, or research only on a relatively narrow time period or geographic scale. Designed to complement large-scale excavations at single sites, CPT is ideal for multi-scalar research that works in tandem with remote sensing techniques, providing samples for detailed laboratory analyses and offering a bridge between surface surveys and large-scale excavation. Given the threats facing archaeological sites around the world from climate change and human development, as well as financial, training and infrastructure constraints, and concerns from many Indigenous communities about large excavations, we argue that CPT is an important method for addressing 21st century human-environmental research questions.